2020
DOI: 10.1038/s41467-020-16781-w
|View full text |Cite
|
Sign up to set email alerts
|

Impaired peroxisomal import in Drosophila oenocytes causes cardiac dysfunction by inducing upd3 as a peroxikine

Abstract: Aging is characterized by a chronic, low-grade inflammation, which is a major risk factor for cardiovascular diseases. It remains poorly understood whether pro-inflammatory factors released from non-cardiac tissues contribute to the non-autonomous regulation of age-related cardiac dysfunction. Here, we report that age-dependent induction of cytokine unpaired 3 (upd3) in Drosophila oenocytes (hepatocyte-like cells) is the primary non-autonomous mechanism for cardiac aging. We show that upd3 is significantly up-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 70 publications
2
41
0
Order By: Relevance
“…Oenocytes are hepatocyte-like cells that are highly enriched with peroxisomes 19, 33 . In addition, the oenocyte peroxisome was identified as an important regulator for age-related production of inflammatory factor, unpaired 3 (upd3) 19 , which could dampen cardiac function non-autonomously. To study cellular responses induced by peroxisomal stress, we performed transcriptomic analysis from Drosophila oenocytes and human cell cultures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oenocytes are hepatocyte-like cells that are highly enriched with peroxisomes 19, 33 . In addition, the oenocyte peroxisome was identified as an important regulator for age-related production of inflammatory factor, unpaired 3 (upd3) 19 , which could dampen cardiac function non-autonomously. To study cellular responses induced by peroxisomal stress, we performed transcriptomic analysis from Drosophila oenocytes and human cell cultures.…”
Section: Resultsmentioning
confidence: 99%
“…Consistently, our translatomic study shows that the majority of peroxisome genes are downregulated in aged fly oenocytes 18 . Our previous study identified that peroxisome import activities in fly oenocytes can non-autonomously regulate cardiac arrhythmia during aging 19 . Several other studies have also implicated that peroxisome is involved in longevity 2022 .…”
Section: Introductionmentioning
confidence: 99%
“…Cannabinoid-2 receptor activation markedly improved hepatic/myocardial inflammation, decreased serum TNF-α level, and cardiac dysfunction, underlining the importance of inflammatory mediators in the pathology of this disease 113 . Hepatocyte-specific knockout of IL-6 was sufficient to block aging-induced cardiac arrhythmia in a fruit fly model 114 . In addition to the characterized linking function of adropin 19 and fetuin 33 , a recent study reported that alpha-1-microglobulin (AMBP) exacerbated inflammation and disturbed hepatic fibrotic repair after myocardial infarction through activating Akt, NF-κB, and ERK signaling and promoting macrophage migration and polarization 115 .…”
Section: Communications Between the Liver And Other Major Organsmentioning
confidence: 97%
“…Like what was shown in terms of gut homeostasis, peroxisome function plays a role in aging-related inflammation induced cardiac disease. Huang et al (2020) showed that reduction in peroxisome protein import in oenocytes, either experimentally by reduction of factors regulating peroxisome import of Pex1, Pex5, or Pex14 activity, disrupted ROS homeostasis cause by Paraquat treatment or due to aging, led to cardiac arrhythmia ( Huang et al, 2020 ). Notably, the age-related effect on the heart could be suppressed by Gal4 > UAS-Pex5 expression in the oenocytes and that the effect was mediated by induction of the cytokine Unpaired 3, a JAK/STAT ligand ( Hombría et al, 2005 ).…”
Section: Developmental Defects Linked To Peroxisome Dysfunction In mentioning
confidence: 99%
“…Notably, the age-related effect on the heart could be suppressed by Gal4 > UAS-Pex5 expression in the oenocytes and that the effect was mediated by induction of the cytokine Unpaired 3, a JAK/STAT ligand ( Hombría et al, 2005 ). Again, this newly discovered role for peroxisome function seems to be conserved between flies and mammals ( Huang et al, 2020 ).…”
Section: Developmental Defects Linked To Peroxisome Dysfunction In mentioning
confidence: 99%